Differential uptake of herpes zoster vaccination associated with socioeconomic status: A population‐based study in Stockholm County, Sweden. Issue 11 (17th September 2018) - Fogelberg, Sara; Lamb, Favelle; Grönlund, Olof; Eriksson, Irene; Sundström, Karin; Clements, Mark; Arnheim‐Dahlström, Lisen
Abstract: Purpose: To investigate whether herpes zoster vaccine (HZV) was associated with socioeconomic status in Stockholm, when the vaccine was reimbursed in Sweden. Methods: This was an observational retrospective case‐control study, using population‐based health care registers. During the study period, September 2013 to November 2014, the HZV was reimbursed as part of the National Pharmaceutical Benefits Scheme in Sweden and recommended for individuals over 50 years. A case was any person, living in Stockholm County, who received HZV during the study period. For each case, 10 (unvaccinated) controls living in Stockholm County were selected and matched by age and sex. In total, 9099 cases and 89 736 controls were included. Socioeconomic variables investigated included education, income, immigration status, and marital status. We also investigated whether HZV was associated with the Charlson Comorbidity Index (CCI), and/or previous herpes zoster diagnosis. Results: Mean age at vaccination was 69.8 years, and 65.8% of vaccinees were women. There was a positive association between vaccination and higher education (OR = 3.4 (95% CI 3.0‐3.8) for men and OR = 2.8 (95% CI 2.6‐3.0) for women, respectively) in comparison to primary education. Higher income and being married were positively associated with vaccination, particularly for men, whereas being an immigrant was negatively associated. There was a negative association between a higher CCI score and HZV, indicating that healthier individuals were more likely to have been vaccinated. Conclusions: Despite the vaccine being part of the National Pharmaceutical Benefit Scheme, receipt of the HZV was significantly associated with socioeconomic factors.